The magic of mining. (Economist, 2015)
The article focuses on the competition within the Bitcoin mining industry in 2015. Topics include the value of the crytptocurrency Bitcoin in 2015, the instability of online currencies, and the hacking of Bitstamp, a Bitcoin exchange, on January 5, 2015. Topics include the lack of regulation of electronic currencies and Bitcoin mining on the cloud.